Criticism and Reflection on Rhythm in Ancient Literary Theory - Yu, Kuo (Transactions on Social Science, Education and Humanities Research, 2024)
This article explores the affirmative and critical views on rhythm in ancient literary theory. In their praise of rhythm, ancient writers saw the importance of its aesthetic value and emotional expression, emphasizing rhythm as the soul of literary art. However, there are also criticisms on issues such as over-restriction of rhythm, creative difficulties, and aesthetic fatigue. Through reflection and comprehensive analysis, we found that rhythm is not only a means of expression in literature, but it may also bring some restrictive problems. Finally, the discussion provides rich lessons and inspirations for contemporary literary creation, encouraging the pursuit of more flexible and diverse expressions while maintaining the beauty of rhythm.